VIABILIDADE ECÔNOMICA SOB CONDIÇÃO DE RISCO DA IMPLANTAÇÃO DE UM SISTEMA AGROSSILVIPASTORIL NO BOLSÃO SUL-MATO-GROSSENSE - da Silva, Mennes Vieira; Lampert, Vinicius do Nascimento; Leite, Rafael da Costa; Alves, Ana Carolina; de Souza, João Paulo Freitas (ANAIS DO ENIC, 2012)